On Bijective Continuous Images of Absolute Null Sets - Kharazishvili, A. (Український математичний журнал, 2015)
The images of absolute null sets (spaces) under bijective continuous mappings are studied. It is shown that, in general, such images do not possess regularity properties from the viewpoint of topological measure theory.